Analysis of Piaget's and Vygotsky's Cognitive Theories and Their Implications for the Sequence of Mathematics Learning Materials - Eko Rahmadani; Bulan Rafika Syafri; Ellis Mardiana Panggabean; Tua Halomoan Harahap (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to analyze the cognitivism theories of Jean Piaget and Lev Vygotsky and their implications for sequencing mathematics learning materials through a systematic literature review approach. Piaget’s theory emphasizes individual cognitive development through the stages of sensorimotor, preoperational, concrete operational, and formal operational, while Vygotsky’s theory highlights the role of social interaction, the Zone of Proximal Development (ZPD), and scaffolding in the learning process. The findings indicate that effective mathematics learning requires the integration of both perspectives, in which learning materials must be aligned with students’ cognitive development and presented progressively from concrete experiences to visual representations and ultimately to abstract mathematical symbols. This process is strengthened through social interaction, discussion, and appropriate scaffolding. This study proposes a systematic sequence model for mathematics learning materials, namely: concrete experience ? visual representation (semi-concrete) ? abstract mathematical symbols ? conceptual generalization ? complex problem solving. This model has been shown to support the development of conceptual understanding, reasoning ability, and learner independence. The findings provide both theoretical and practical contributions for teachers and curriculum developers in designing mathematics instruction that is developmentally appropriate, interactive, and meaningful